Influence of rib impact on thoracic gunshot trauma. Issue 6 (8th August 2018) - Rodrigues, Samantha Alda; Guey, J; Plummer, T C H; Pullen, A; Shaw, B; Kieser, D C
Abstract : Introduction: The influence of rib impact on thoracic gunshot trauma remains unclear, despite its high occurrence. This study therefore investigates the effect of rib impact on a bullet's terminal properties and injury severity. Methods: Two bullets were used: 5.56×45 mm (full charge and reduced charge) and 7.62×51 mm (full charge). For each bullet, three impact groups were tested: (1) plain 10% ballistic gelatin (control) conditioned at 4°C, (2) intercostal impact, and (3) rib impact, the latter two tested with samples of porcine thoracic walls embedded in gelatin. Analysis included penetration depth, trajectory change, yaw, fragmentation, velocity reduction, energy deposition and temporary and permanent cavity characteristics. Results: No significant differences were observed for most variables. Differences were found between rib (and intercostal) impact and the control groups, suggesting that the inclusion of thoracic walls produces an effect more significant than the anatomical impact site. Effects were ammunition specific. For the 7.62×51 mm round, rib impact caused an earlier onset of yaw and more superficial permanent gelatin damage compared with plain gelatin. This round also formed a larger temporary cavity on rib impact than intercostal impact. Rib (and intercostal impact) created a smaller temporary cavity than the control for the 5.56×45 mm round. For the reduced-charge 5.56×45 mm round, rib and intercostal impact produced greater velocity reduction compared with plain gelatin. Conclusions: This study provides new insights into the role of rib impact in thoracic gunshot injuries, and indicates that the effects are ammunition dependent. Unlike the 5.56×45 mm rounds, rib impact with the 7.62×51 mm rounds increases the risk of severe wounding.